UTILIZING BIOTOPE PRINCIPLES AND TECHNIQUES FOR SUSTAINABLE CULTIVATION AND DOMESTICATION OF AN ENDANGERED PAROSPHROMENUS DEISSNERI - Valen, Fitri Sil; Notonegoro, Hartoyo; Sitorus, Rostiar (Journal of Aquatropica Asia, 2024)
Parosphromenus deissneri is a freshwater species known exclusively from Bangka Island, Indonesia. According to the IUCN Red List of Threatened Species in 2020, this species is endangered, and the population continues to decrease due to the consequences of open-pit tin mining on Bangka Island harming its natural ecosystem. Despite the fact that this species is regarded as endangered, no known conservation and domestication initiatives have been made to enhance its number in the wild. In this study, we propose to do domestication of P. deissneri using biotope principles and techniques to increase the P. deissneri capacity for adaptation and reproduction since these species believe they are in their natural habitat. This study was carried out from April to September of 2023 at Bangka Belitung Endemic Fish Laboratory. We designed the biotope concept using an aquarium with dimensions 200 cm x 100 cm x 50cm. Biotopes are equipped with aquatic plants, roots, twigs, dead leaves, sand, rocks, gravel, and water containing natural plankton as biotic and abiotic elements. In this study, a Parosphromenus deissneri broodstock of 20 individuals (10 males and 10 females) was maintained for a 5-month period, resulting in an 80% survival rate. During the study, one mating pair successfully produced approximately 14 eggs, 8 of which hatched. Following a 2-month larval development phase, 4 fry survived to adulthood, yielding a survival rate of 25% relative to the total number of hatched eggs. These results underscore the necessity for refined husbandry practices and optimal environmental conditions to improve fry survival and enhance reproductive success in future breeding efforts.